Artists of the John Reed Club in the USSR: The History of Forgotten Cultural Ties of the Late 1920s and Early 1930s - Bulatov, Danila A. (Actual Problems of Theory and History of Art, 2020)
This paper is devoted to a poorly studied question of the emergence, in the late 1920s and early1930s, of strong ties between Soviet cultural institutions and American ‘revolutionary’ artists that primarily worked in left-leaning periodicals (such as The New Masses and The Daily Worker) and began to unite in the John Reed Clubs following the outbreak of the Great Depression. Against a backdrop of a whole range of problems in the economic and social system of the USA, the USSR attracted American left-wing artists and intellectuals as a country that had eliminated the barriers of class, ethnicity, and race, and where culture was created by workers for the working class. Their sympathies for the USSR derived to a certain extent from the paternalistic model of interrelationship between the authorities and art that had developed there, and which they could only dream of in the middle of the crisis. In 1929, the first and most influential John Reed Club was established in New York, soon to become affiliated with the Comintern and begin implementing its directives.Focusing on the exhibitions of the John Reed Club artists that took place in the Soviet Union between 1931and 1936, this paper also examines the interconnections between American artists with leftist sympathies and various Soviet institutions, among which are VOKS (All-Union Society for Cultural Relations with Foreign Countries), IBRA (International Bureau of Revolutionary Artists) and GMNZI (State Museum of New Western Art). Other goals of the paper are to follow up on the transformation of the very concept of ‘revolutionary art,’ occurring both in the USSR and the USA, and to trace the reception of American political art by Soviet critics in the decisive years of formation of the socialist realism canon.
Keywords: cultural relations; John Reed Club; social realism; American art; leftist art; revolutionary art; political satire; VOKS; Museum of New Western Art; International Bureau of Revolutionary Artists; Comintern